Melting and solidification characteristics of a double-pipe latent heat storage system with sinusoidal wavy channels embedded in a porous medium. (15th March 2019) - Shahsavar, Amin; Al-Rashed, Abdullah A.A.A.; Entezari, Sajad; Sardari, Pouyan Talebizadeh
Abstract: The aim of this investigation is to explore the combined effects of porous medium and surface waviness on the melting and solidification of PCM inside a vertical double-pipe latent heat storage (LHTES) system. The results are compared with the cases of smooth channels and pure PCM. In the system, water is passed through the inner tube while composite PCM is placed in the annulus side. Different effective parameters including wavelength and wave amplitude of the sinusoidal wavy channels, porosity and pore size of the porous structure, Reynolds number and inlet temperature of water are examined to find the optimum geometric as well as operating conditions in both melting/solidification processes. The results show that utilizing both the high conductive porous structure and wavy channel reduces the melting/solidification times significantly. For the best case, the melting and solidification times of PCM reduce by 91.4% and 96.7%, respectively, compared with the smooth channels pure PCM system. The average rate of transferred heat for the wavy channel composite PCM are 10.4 and 18.9 times that for the smooth channel pure PCM case. Comparing with the pure PCM system, the presence of copper foam reduces the effect of channel waviness significantly for both melting/solidification processes. Highlights: Study of a vertical double-pipe LHTES system with sinusoidal wavy channels. Comparison of a composite metal foam-PCM LHS system with the pure PCM case. Present the advantages of the porous medium on melting and solidification times. Analysis of the distributions of liquid fraction and temperature and pressure drop. Analysis of rate of transferred heat, TES rate, TES density and TES rate density.